A companion to American legal history - Brophy, Alfred L.; Hadden, Sally E. (Wiley-Blackwell companions to American history, 2013)
Presents up-to-date research describing key debates in American legal history Reflects the current state of American legal history research and points readers in the direction of future research Represents an ideal companion to graduate and law students seeking an introduction to the field, the key questions, and future research ideas